2020
DOI: 10.3390/ijerph17072450
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Elixhauser and Charlson Methods for Discriminative Performance in Mortality Risk in Patients with Schizophrenic Disorders

Abstract: Although Charlson Comorbidity Index scores (CCIS) and Elixhauser comorbidity index scores (ECIS) have been used to assess comorbidity in patients with schizophrenia, only CCIS, not ECIS, have been used to predict mortality in this population. This nationwide retrospective study investigated discriminative performance of mortality of these two scales in patients with schizophrenia. Exploiting Taiwan’s National Health Insurance Research Database (NHRID), we identified patients diagnosed with schizophrenia discha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 42 publications
1
12
0
Order By: Relevance
“…We found that including comorbidities from the previous year when calculating the Charlson and Elixhauser score improved model fit when each was considered individually, implying superior control of confounding, compared with only using comorbidities recorded in the diagnostic-dominant episode. The Elixhauser score was more prognostic than the Charlson score when using one score to adjust for risk of 30-day mortality, as shown in previous studies (6,(18)(19)(20)(22)(23)(24)(25)(26)(27)(28)(29). However, we found that including both comorbidity scores together with their interaction, and incorporating non-linear effects, provided the best model fit.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…We found that including comorbidities from the previous year when calculating the Charlson and Elixhauser score improved model fit when each was considered individually, implying superior control of confounding, compared with only using comorbidities recorded in the diagnostic-dominant episode. The Elixhauser score was more prognostic than the Charlson score when using one score to adjust for risk of 30-day mortality, as shown in previous studies (6,(18)(19)(20)(22)(23)(24)(25)(26)(27)(28)(29). However, we found that including both comorbidity scores together with their interaction, and incorporating non-linear effects, provided the best model fit.…”
Section: Discussionsupporting
confidence: 75%
“…The resulting modified single score (17) used diagnostic codes from the current admission with a "type" indicating preadmission comorbidity (analogous to those from the diagnosis-dominant episode), and comorbidities from all previous hospital admissions, implying other studies do the same. A systematic review of 54 papers prior to March 2011 found the Elixhauser score to generally be superior to Charlson (18); a conclusion echoed by studies since (6,(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30). However, none of these studies combined the scores in their validated forms in one model, and this does not seem to have been considered in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…We identified 59 studies for the topic of in-hospital mortality. 117 118 119 120 121 122 123 124 125 126 127 128 129 130 131 132 133 134 135 136 137 138 139 140 141 142 143 144 145 146 147 148 149 150 151 152 153 154 155 156 157 158 159 160 161 162 163 164 165 166 167 168 169 170 171 172 173 174 175 While the majority of studies used a retrospective cohort design, 11 used a prospective approach, 120 122 129 140 143 166 169 170 172 174 175 and two were meta-analysis studies. 154 …”
Section: Resultsmentioning
confidence: 99%
“…154 157 The majority of studies used EHR data, while 16 studies used some kind of registry data, 117 118 121 127 128 131 132 138 140 141 142 150 153 155 156 161 174 four studies used questionaries/surveys, 166 169 170 172 and two studies used administrative data. 134 167 With the emergence of public databases containing COVID-19 data, since 2020, many studies used these databases for their studies. 120 123 128 131 140 142 143 146 169 Study populations primarily comprised adults (sometimes limited to subpopulations such as those with chronic illnesses [e.g., Takada et al 164 and Sukmark et al 163 ]), but three studies included pediatric populations, 138 154 161 one study included newborns, 150 and two studies included elder patients aged over 65 years.…”
Section: Resultsmentioning
confidence: 99%
“…One year after the implementation of the Charlson Comorbidity Index, researcher Elixhauser and colleagues introduced a new model for estimating the comorbidity index, The Elixhauser Comorbidity Index (ECI). The ECI is suitable for studying data from administrative databases, such as the hospitalization database, and it includes 31 comorbidities ( 7 , 8 ).…”
Section: Introductionmentioning
confidence: 99%